2020
DOI: 10.1111/ssqu.12796
|View full text |Cite
|
Sign up to set email alerts
|

Combat Experience and the Foreign Policy Positions of Veterans

Abstract: ObjectivePrior work on the effect of combat on veterans typically measures combat experience as a dichotomous event. I extend work in this area by theorizing and empirically accounting for the number of unique combat experiences a veteran endures and how that associates with the veteran's outlook on foreign policy.MethodsI utilize an original survey that asks for multiple types of military combat experience, as well as foreign policy positions.FindingsConsistent with previous research, I find that veterans ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…While these studies are interesting, they tell us only about elite foreign/military policy beliefs. More recently, Endicott (2020) shows, consistent with the work on leaders by Horowitz and Stam (2014), that military veterans tend to be more hawkish than non-veterans, but that this effect is mitigated by combat experience. Other recent studies have worked to expand on Gelpi and Feaver’s population of interest by focusing on active servicemembers and cadets in the service academies.…”
Section: Previous Researchmentioning
confidence: 65%
“…While these studies are interesting, they tell us only about elite foreign/military policy beliefs. More recently, Endicott (2020) shows, consistent with the work on leaders by Horowitz and Stam (2014), that military veterans tend to be more hawkish than non-veterans, but that this effect is mitigated by combat experience. Other recent studies have worked to expand on Gelpi and Feaver’s population of interest by focusing on active servicemembers and cadets in the service academies.…”
Section: Previous Researchmentioning
confidence: 65%
“…To date, contemporary social scientists have tended to pay greater attention to the role of military service in shaping subsequent life-course transitions (Landes, London, and Wilmoth 2021;MacLean and Elder 2007;Werum et al 2020) than to the potential influence of military background on various facets of civic engagement and public opinion. This imbalance is unfortunate because the latter works have shown important links between military service and (a) civic and political participation and (b) political attitudes, particularly regarding those issues that have particular relevance with respect to the military (Ellison 1992;Endicott 2020;Wilson and Ruger 2021). It is beyond time to reinvigorate the sustained social scientific study of military training and experience as they bear upon the lives of veterans, their families, and their communities.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in this domain have long recognized that military service, and especially combat experiences, are often life‐changing events, turning points that can have a range of long‐term consequences as veterans return to civilian life (Elder 1986; Laufer 1988). Thus, investigators over the years have distinguished between the effects of military training in general and combat experience in particular in shaping political attitudes and civic and political engagement upon return to civilian life (Ellison 1992; Endicott 2020; Wilson and Ruger 2021). Although some early studies concluded that the effects of military service on political attitudes and behavior were minimal (e.g., Jennings and Markus 1977), subsequent research has shown that veterans, especially combat veterans, are more likely to volunteer for community affairs, vote, and engage in more high‐initiative political behavior, such as participating in campaigns, than nonveterans from otherwise similar backgrounds (Ellison 1992; Leal and Teigen 2018; Wilson and Ruger 2021).…”
Section: The Military and Social Sciencesmentioning
confidence: 99%
See 1 more Smart Citation